2016
DOI: 10.1038/srep21728
|View full text |Cite
|
Sign up to set email alerts
|

The intertropical convergence zone modulates intense hurricane strikes on the western North Atlantic margin

Abstract: Most Atlantic hurricanes form in the Main Development Region between 9°N to 20°N along the northern edge of the Intertropical Convergence Zone (ITCZ). Previous research has suggested that meridional shifts in the ITCZ position on geologic timescales can modulate hurricane activity, but continuous and long-term storm records are needed from multiple sites to assess this hypothesis. Here we present a 3000 year record of intense hurricane strikes in the northern Bahamas (Abaco Island) based on overwash deposits i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 63 publications
(100 reference statements)
12
111
0
Order By: Relevance
“…Furthermore, one of the intervals with the highest TC activity in the Vieques reconstruction occurred between 2,500 y and 1,000 y BP, when the flux of Saharan dust was low compared with that in the subsequent millennium (44). Other evidence supportive of the results presented here includes a recent study (45) highlighting the link between reduced dust loading during the early and mid-Holocene and the northward expansion of the ITCZ, which in turn can intensify TC activity in the western North Atlantic (37). The message from these paleoclimatic studies is that the Saharan dust layer appears to suppress TC activity, consistent with the inverse relationship between Saharan dust emission and Atlantic TC activity found in instrumental records (9,46).…”
Section: Atl Epsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, one of the intervals with the highest TC activity in the Vieques reconstruction occurred between 2,500 y and 1,000 y BP, when the flux of Saharan dust was low compared with that in the subsequent millennium (44). Other evidence supportive of the results presented here includes a recent study (45) highlighting the link between reduced dust loading during the early and mid-Holocene and the northward expansion of the ITCZ, which in turn can intensify TC activity in the western North Atlantic (37). The message from these paleoclimatic studies is that the Saharan dust layer appears to suppress TC activity, consistent with the inverse relationship between Saharan dust emission and Atlantic TC activity found in instrumental records (9,46).…”
Section: Atl Epsupporting
confidence: 70%
“…Previous modeling studies (30,31) found that although the TC genesis potential during the MH decreased in the NH under stronger summer insolation, it increased in the SH under weaker summer insolation relative to the preindustrial (PI) climate. However, PMIP model simulations for the MH do not adequately reproduce the intensification and geographical expansion of the WAM (35) and ISM (36), as inferred from proxy archives, or the shift in the Intertropical Convergence Zone (ITCZ) position, which can have a pronounced influence on TC development (37). Recent modeling efforts have shown that accounting for extensive greening of the Sahara and the associated reduction of dust emissions allows for better simulation of the WAM strengthening (18,38) and its teleconnections (39,40).…”
mentioning
confidence: 99%
“…4c) away from the western Caribbean. This effect is superimposed on a southward migration of the MDR, which tracks the southward migration of the ITCZ5. The abrupt western Caribbean TC decrease at ~1870 may reflect a shift to more northerly recurving tracks47 for one or two Cape Verde storms per year that had previously impacted the Yok Balum Cave site, a scenario supported by contemporaneous TC activity increases at more northeasterly sites such as Bermuda and Florida27 (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Observational and modelling studies suggest that the recent multidecadal trend of rising sea surface temperatures (SST) in the North Atlantic’s Main Development Region (MDR) may have increased Atlantic tropical cyclone (TC) intensity and duration123, and shifted storm tracks poleward45. Some studies ascribe this oceanic warming to a multi-decadal SST periodicity known as the Atlantic Multidecadal Oscillation (AMO)67 associated with the strength of thermohaline circulation78 or large-scale atmospheric circulation910, while others implicate rising anthropogenic greenhouse gases (GHGs)1112.…”
mentioning
confidence: 99%
“…[ Kistler et al , ; Whitlock et al , ] suggests winds reaching the high Andes (Ecuador) today largely originate from the tropical Atlantic, with only a very moderate relationship of rainfall to ENSO [ Mora and Willems , ] near Laguna Pallcacocha. Van Hengstum et al [, and references therein] suggest that runoff at Laguna Pallcacocha may be related to ITCZ variability, consistent with Caribbean vegetation/rainfall records and phasing of North Atlantic hurricane activity, which is enhanced when the northern edge of the ITCZ migrates toward the Main Development Region (~20–80°W, 10–20°N). A more compressed (extensive) seasonal range of the ITCZ around the equator during periods of low (high) multidecadal Pacific SST variability could potentially explain the apparent anticorrelation of the Laguna Pallcacocha record and high‐frequency Ti/Ca variability at Tahaa.…”
Section: Resultsmentioning
confidence: 70%